Inhibition of human immunodeficiency virus type 1-induced cell fusion by recombinant human interferons. - Wells, D E (1991)
Pretreatment of HeLa T4 cells with recombinant alpha, beta, or gamma interferon (IFN) was found to significantly inhibit syncytium formation induced by the human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein. All three IFNs were found to be potent inhibitors of fusion in a system in which Spodoptera frugiperda cells, infected with a baculovirus recombinant expressing the HIV-1 envelope protein, were cocultivated with HeLa T4 cells. In addition, these IFNs were also found to block HeLa T4 cell fusion induced by the HIV-1 envelope proteins expressed from a vaccinia virus recombinant. Furthermore, the IFNs inhibited cell fusion between HIV-1 envelope glycoprotein-expressing cells and either immortalized or fresh CD4+ lymphocytes pretreated with the IFNs. These results suggest that further testing of human IFNs for therapy of HIV-1 infection will be of interest.